One Amongst Many: higher education institutions in an ecosystem of urban pedagogies - Geetika Anand; Ruchika Lall; Julia Wesely; Adriana Allen (Universidade Federal do Rio Grande do Sul, 2022)
This paper explores how and why pedagogues within universities can and need to work as 'one amongst many' to advance critical pedagogies for urban equality. The discussion draws on two contrasting experiences: the networked schools of the Habitat International Coalition in Latin America (HIC-AL) - a coalition of civil society organizations, social movements and universities working in defense of habitat-related human rights - and the co-learning processes with housing rights activists activated by the Indian Institute for Human Settlements (IIHS) - a national education institution committed to the equitable, sustainable and efficient transformation of Indian settlements. Both experiences place emphasis on crafting critical pedagogies that seek to fundamentally disrupt, re-frame and re-position institutional relations of knowledges and learning practices, while advancing capacities for transformative urban change. The analysis demonstrates how epistemic injustices - often proliferated in and by higher education institutions - can be counteracted, and why fostering epistemic justice requires re-positioning universities as one amongst many in a wider ecosystem of urban pedagogies, in open and productive dialogue with new institutional forms that Boaventura de Sousa Santos defines as the 'pluriversity' and the 'subversity'.